2016
DOI: 10.1016/s2213-2600(16)30149-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeted case finding for chronic obstructive pulmonary disease versus routine practice in primary care (TargetCOPD): a cluster-randomised controlled trial

Abstract: Word count: 4222 3 RESEARCH IN CONTEXT Evidence before this studyIt is widely accepted that COPD is substantially under-diagnosed worldwide. Mass population screening with spirometry is not recommended although early identification of undiagnosed patients with clinical disease is generally supported because COPD has significant patient, healthcare and societal burden which could potentially be lessened through timely diagnosis. A comprehensive systematic review of the effectiveness of case-finding studies, pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 26 publications
5
88
0
1
Order By: Relevance
“…However, the true COPD rate within the screened population may be higher due to the likelihood that some cases were missed as a result of the high non‐attendance rate at 1‐stop clinics among current and ex‐smokers. Published reports of primary care based targeted COPD case finding demonstrate a diagnosis rate of between 2% and 20% . There are, however, fundamental differences in methodology, with the screening intervention we describe being short‐term, labour‐intensive and combined with a public awareness campaign.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, the true COPD rate within the screened population may be higher due to the likelihood that some cases were missed as a result of the high non‐attendance rate at 1‐stop clinics among current and ex‐smokers. Published reports of primary care based targeted COPD case finding demonstrate a diagnosis rate of between 2% and 20% . There are, however, fundamental differences in methodology, with the screening intervention we describe being short‐term, labour‐intensive and combined with a public awareness campaign.…”
Section: Discussionmentioning
confidence: 91%
“…It is also important to consider regional variation in smoking and COPD prevalence when considering the effectiveness of different case finding initiatives. Practice‐based targeted case finding in the United Kingdom has been demonstrated to be cost‐effective . No cost‐effectiveness analysis was performed as part of our evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers exposed to smoke have a higher risk of developing COPD (1.64; 95% CI, 1.25-2.14) than non-exposed individuals 25 , so it is reasonable to argue that a search strategy applied to identify cases, instead of simply diagnosing symptomatic patients, would bring greater benefits to the general population. A strategy designed to detect asymptomatic COPD cases found that in at-risk individuals over 35 years old, this was more effective 26 , especially if a spirometry is combined with a questionnaire 27 28 . A study conducted in Japan that applied a screening strategy to detect cases with follow-up on patients aged 40 and over in the form of regular visits and use of a portable spirometer generated a sensitivity of 40.7%, a specificity of 96.4%, a PPV of 78.6%, and an NPV of 83.5% 29 .…”
Section: Case Finding and Screening For Copdmentioning
confidence: 99%
“…Although population screening is not recommended in the general population (18), targeted case finding may be an alternative to detect patients who may be at increased risk for COPD (19). In particular, several questionnaires have been evaluated to have a role in identification of the disease (20).…”
mentioning
confidence: 99%